Community-based integrated natural resource management in Okyeman traditional area of the Eastern region, Ghana: Socio-economic profile of the Okyeman traditional area - Ayivor, J.S.; Ekpe, E. (West African Journal of Applied Ecology, 2012)
The Akyem Abuakwa State, otherwise referred to as the Okyeman traditional area, in historic times, struggled against dominant groups like the Ashantis to gain self recognition. In present times, the state has remained resolute and constitutes a strong and influential traditional authority in Ghana. The Okyeman traditional area is located in the Eastern Region of Ghana. It is endowed with rich natural resources including forest, mineral and water resources. In a survey to examine the socio-economic profile of the area and how traditional practices and taboos affect natural resource use, 426 respondents from 33 communities were randomly sampled and interviewed through questionnaire administration. The results of the analysis indicated that about 72% of the population was engaged in farming. The results also showed that traditional practices and taboos had played significant roles in natural resource management in the past, but being abandoned presently because of divergent beliefs. It was further revealed that rapid population growth from the 1960s to date and its associated production pressures was a major underlying factor in resource exploitation in the area. The activities of small-scale miners in particular were observed to be the major source of stream pollution and flow regime disturbance. The hitherto rich biodiversity of the area is at risk of being eroded if urgent steps are not taken to stop illegal activities in surrounding forest reserves. The study recommended the provision of alternative livelihood opportunities to the farming population to safeguard the rich forest resources and water bodies from further degradation.
Keywords: Community-based; integrated natural resource management; Okyeman traditional area; Ghana; Eastern region